Subacute effects of the number of Pilates exercise series on cardiovascular responses in hypertensive women - Jocarla C Chagas; Rodrigo Miguel-; Afrânio A Bastos; Evaleide D Oliveira; Valter J Santana-Filho; Rogério B Wichi (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aim: To evaluate the subacute effects of the number of Pilates exercise series (one and three) on the cardiovascular responses of medicated hypertensive women. Methods: Eight hypertensive and nine normotensive women underwent a Pilates session with low and high volume, and cardiovascular responses were measured. Aged sample of 50-65 years old underwent to anthropometrical measurements previously to the experimental procedures. The cardiovascular assessment was performed before and after every experimental session. The experimental procedures consisted of two familiarization sessions, load determination, and two experimental sessions (one or three series) for each group. Results: In the intragroup analysis, HR was found to be reduced in the normotensive group. In the hypertensive group, a reduction in the double product was observed after both Pilates sessions, and in the normotensive group only after the session with one series. The volume of exercises of the Pilates method did not interfere in the responses of systolic and diastolic BP after exercise. However, a more prominent area under the curve was seen in the systolic BP of hypertensive subjects who performed three series. Conclusion: The present study shows that performing one or three series of the Pilates exercise does not induce hypotension post-exercise and did not interfere in the cardiovascular responses of medicated hypertensive women.